2018
DOI: 10.1186/s40594-018-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

The nature of science identity and its role as the driver of student choices

Abstract: BackgroundA major concern in science education involves the under-representation of many groups in science and technology fields, especially by gender (Brotman and Moore, J Res Sci Teach 45:971–1002, 2008; Clark Blickenstaff, Gend Educ 17:369–386, 2006), stemming from an intersection of systemic obstacles (Cantú, Equity Excell Educ 45:472–487, 2012; Rosa and Mensah, Phys Rev Phys Educ Res 12:020113, 2016). Research on persistence of minoritized populations within science trajectories has often highlighted iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 46 publications
1
134
0
5
Order By: Relevance
“…We developed a survey tool based on published literature and previously used instruments which included measures of STEM belonging (Lewis et al, 2017), science identity (Vincent-Ruz & Schunn, 2018), and growth mindset (Rattan et al, 2015;Leslie, Cimpian, Meyer, & Freeland, 2015), as well as measures assessing students' views on their STEM participation. The Institutional Review Board (IRB) indicated the study is exempt under 45 Code of Federal Regulations (CFR) § 46.104(d)(2) because this is an anonymous survey study.…”
Section: Methodsmentioning
confidence: 99%
“…We developed a survey tool based on published literature and previously used instruments which included measures of STEM belonging (Lewis et al, 2017), science identity (Vincent-Ruz & Schunn, 2018), and growth mindset (Rattan et al, 2015;Leslie, Cimpian, Meyer, & Freeland, 2015), as well as measures assessing students' views on their STEM participation. The Institutional Review Board (IRB) indicated the study is exempt under 45 Code of Federal Regulations (CFR) § 46.104(d)(2) because this is an anonymous survey study.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly discussed value components are intrinsic value (enjoyment) and utility value (usefulness). When individuals perceive a task or domain as intrinsically valuable or extrinsically valuable to their goals, this can promote better engagement and motivation [33,63,69,94]. Intrinsic value in the original model is now often discussed as interest, which is defined by positive emotions accompanied by curiosity and engagement in the particular content [95][96][97].…”
Section: B Motivational Factors That Are the Foundations Of Studentsmentioning
confidence: 99%
“…Science and STEM identity has a complex differential function in supporting students' optional science choices by gender, and STEM identity may be associated with academic performance and flourishing in undergraduate physics courses at the end of the term, particularly for women (Seyranian et al, 2018;Vincent-Ruz & Schunn, 2018). In mathematical problem solving, the role of selfefficacy beliefs and the nature of science identity has also been widely investigated (Pajares & Miller, 1994;Pajares & Urdan, 2006;Vincent-Ruz & Schunn 2018;Zeldin & Pajares, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Science and STEM identity has a complex differential function in supporting students' optional science choices by gender, and STEM identity may be associated with academic performance and flourishing in undergraduate physics courses at the end of the term, particularly for women (Seyranian et al, 2018;Vincent-Ruz & Schunn, 2018). In mathematical problem solving, the role of selfefficacy beliefs and the nature of science identity has also been widely investigated (Pajares & Miller, 1994;Pajares & Urdan, 2006;Vincent-Ruz & Schunn 2018;Zeldin & Pajares, 2000). In their longitudinal study, Parker, Marsh, Ciarrochi, Marshall, and Abduljabbar (2014) found (a) a strong relationship between achievement, self-efficacy, and self-concept in mathematics at age 15; (b) both selfconcept and self-efficacy being independent and similarly strong predictors of tertiary entrance ranks at the end of high school; (c) math self-efficacy as a significant predictor of university entry but math self-concept was not; and (d) math self-concept as a significant predictor of undertaking post-school studies in science, technology, engineering, or math, but math self-efficacy was not.…”
Section: Introductionmentioning
confidence: 99%